Analisis Kompetensi Aparatur Terhadap Sistem Pengelolaan Keuangan Daerah di Desa Trimurjo - Darma Krisnanto; Nadia Anggraeni; Patricia Amanda Pertiwi (International Forum of Researchers and Lecturers, 2025)
The aim of this research is to see how the ability of village officials has an impact on the regional financial management system in Trimurjo Village, Central Lampung Regency. The involvement of the apparatus in question includes the knowledge, skills and attitudes needed to carry out their duties and responsibilities. This study is based on the theoretical framework of Spencer & Spencer (1993) and the principles of regional financial management according to Minister of Home Affairs Regulation No. 13 of 2006, emphasizes the importance of competency to ensure that village fund management runs well and efficiently. This research was conducted qualitatively, with data collected through interviews and literature study. The research results show that the competency of Trimurjo village officials in financial management still needs to be improved. The most significant factor is knowledge of the apparatus. This research proposes sustainable training and development to improve the quality of village financial management.